Bioactive Natural Products in Actinobacteria Isolated in Rainwater From Storm Clouds Transported by Western Winds in Spain - Sarmiento-Vizcaíno, Aida; Martín, Jesús; Reyes, Fernando; García, Luis A.; Blanco, Gloria (Frontiers in Microbiology, 2021)
Actinobacteria are the main producers of bioactive natural products essential for human health. Although their diversity in the atmosphere remains largely unexplored, using a multidisciplinary approach, we studied here 27 antibiotic producing Actinobacteria strains, isolated from 13 different precipitation events at three locations in Northern and Southern Spain. Rain samples were collected throughout 2013-2016, from events with prevailing Western winds. NOAA HYSPLIT meteorological analyses were used to estimate the sources and trajectories of the air-mass that caused the rainfall events. Five-day backward air masses trajectories of the diverse events reveals a main oceanic source from the North Atlantic Ocean, and in some events long range transport from the Pacific and the Arctic Oceans; terrestrial sources from continental North America and Western Europe were also estimated. Different strains were isolated depending on the precipitation event and the latitude of the sampling site. Taxonomic identification by 16S rRNA sequencing and phylogenetic analysis revealed these strains to belong to two Actinobacteria genera. Most of the isolates belong to the genus Streptomyces and 16 more species were here identified, thus increasing to more than 5 % the number of species of this genus isolated from the atmosphere. Furthermore, five strains belonging to the rare Actinobacterial genus Nocardiopsis were isolated in some events. These results reinforce our previous Streptomyces atmospheric dispersion model, which we extend herein to the genus Nocardiopsis. Production of bioactive secondary metabolites was analyzed by LC-UV-MS. Comparative analyses of Streptomyces and Nocardiopsis metabolites with natural product databases led to the identification of multiple, chemically diverse, compounds. Among bioactive natural products identified 55% are antibiotics, both antibacterial and antifungal, and 23% have antitumor or cytotoxic properties; also compounds with antiparasitic, anti-inflamatory, immunosupresive, antiviral, insecticidal, neuroprotective, anti-arthritic activities were found. Our findings suggest that over time, through samples collected from different precipitation events, and space, in different sampling places, we can have access to a great diversity of Actinobacteria producing an extraordinary reservoir of bioactive natural products, from remote and very distant origins, thus highlighting the atmosphere as a contrasted source for the discovery of novel compounds of relevance in medicine and biotechnology.